Ni Nanoparticles on Reducible Metal Oxides (Sm2O3, CeO2, ZnO) as Catalysts for CO2 Methanation - Athirah Ayub; Hasliza Bahruji; Abdul Hanif Mahadi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
The activity of reducible metal oxide Sm2O3, CeO2, and ZnO as Ni nanoparticles support was investigated for CO2 methanation reaction. CO2 methanation was carried out between 200 °C to 450 °C with the optimum catalytic activity was observed at 450 °C. The reducibility of the catalysts has been comparatively studied using H2-Temperature Reduction Temperature (TPR) method. The H2-TPR analysis also elucidated the formation of surface oxygen vacancies at temperature above 600 °C for 5Ni/Sm2O3 and 5Ni/CeO2. The Sm2O3 showed superior activity than CeO2 presumably due to the transition of the crystalline phases under reducing environment. However, the formation of NiZn alloy in 5Ni/ZnO reduced the ability of Ni to catalyze methanation reaction. A highly dispersed Ni on Sm2O3 created a large metal/support interfacial interaction to give 69% of CO2 conversion with 100% selectivity at 450 °C. The 5Ni/Sm2O3 exhibited superior catalytic performances with an apparent phase transition from cubic to a mixture of cubic and monoclinic phases over a long reaction, presumably responsible for the enhanced conversion after 10 h of reaction. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).